Dream Enactment Behavior Disorder Associated with Pallido‐Nigro‐Luysian Degeneration and Tau Proteinopathy. Issue 4 (29th March 2021) - Di Luca, Daniel G.; Slow, Elizabeth J.; Martinez‐Valbuena, Ivan; Lang, Anthony E.; Kovacs, Gabor G.
ABSTRACT: Background: Pallido‐nigro‐luysian atrophy (PNLA) is a rare neurodegenerative disorder with only a few cases reported to date. Although the clinical picture usually resembles progressive supranuclear palsy, pathological examination reveals more selective atrophy and loss of neurons in the globus pallidus, substantia nigra and subthalamic nucleus. Objectives: To describe the clinical features and pathological findings of a patient with PNLA. Methods: Case report with clinico‐pathological discussion. Results: An 83‐year‐old man presented to our clinic with a vertical supranuclear gaze palsy, parkinsonism, gait impairment and sleep abnormalities suggestive of REM‐sleep behavior disorder. Neuropathological examination 5 years after symptom onset revealed subcortical tau proteinopathy compatible with a PNLA pattern. There was also an associated mild degree of limbic/subcortical inflammatory response, Alzheimer's disease‐related changes, as well as argyrophilic grain disease. Conclusions: We present a comprehensive clinico‐pathological discussion of a patient with PNLA. Besides parkinsonism and vertical supranuclear gaze palsy, the patient also had a sleep disorder, clinically suggestive of REM behavioral disorder, which has not been previously reported in PNLA. We expand the clinical phenotype of this rare condition and provide neuropathological evidence for the associated abnormalities.